Stresses in the cap of a connecting rod. (November 2021) - Baldini, A.; Strozzi, A.; Bertocchi, E.; Mantovani, S.
Graphical abstract: Highlights: Cap failures in conrod are examined, varies geometries of cap cross section are shown. The stresses within a cap in the presence or absence of ribs are compared. The adoption of ribbed sections may undesirably increase the cap bending stress. An analytical study of the stress field within the cap, validated vs FE, is developed. Connection between load and contact extent is summarized by the new load parameter Ψ. Abstract: In this practically oriented paper, representative examples of cap failures in a connecting rod are discussed, and deeply dissimilar geometries of the cap cross section are presented. An analytical model of the stresses within a connecting rod cap is developed and satisfactorily validated versus FE (Finite Elements). This model accounts for the effect of the initial clearance between the crankpin surface and the cap intrados, and it realistically mimics the crankpin-cap progressive contact. A load parameter that accounts for the combined effects of several leading variables is analytically derived, on which the following variables depend: a) the contact angular extent between the crankpin and the cap; b) the ratio between the normal and bending stress. This model indicates that the cap bending stress depends on the initial gap between the crankpin and the cap, and not on the applied load. The normal stress within the cap is found to be considerably higher than its bending counterpart. The mechanical response of cap rectangular and ribbed cross sections is compared, and it is found that ribbed sections undesirably increase the cap bending stress. Consequently, the employment of ribs appears to be unjustified from a purely stress related viewpoint.